Sovereignty, Reason, and Will: Carl Schmitt and Hasidic Legal Thought - Rothschild, Zalman (Journal of law and religion, 2022)
The decisionistic strand in Jewish legal philosophy is often neglected by scholars focused on the more common rational explanations for Jewish law. This article brings attention to decisionism in Jewish legal thought by analyzing the legal philosophy of Shneur Zalman of Lyady, the founder of the Habad Hasidic movement. The author uses the legal and political thought of Carl Schmitt - arguably modernity's most influential decisionist - to help elucidate Shneur Zalman's decisionistic legal thought and thereby put into sharper focus an otherwise underappreciated current in Jewish legal philosophy.